Utilizing Digital Promotion on the Besek Program for the Besek Kurban - Alfiandi Imam Mawardi; Prihandono Wibowo; Budi Prabowo; Rusdi Hidayat; Praja Firdaus Nuryananda (Future Science, 2022)
The Bekurban program is a program to distribute besek (traditional packaging made of bamboo) from one of the fostered villages of UPN “Veteran” Jawa Timur, namely Tegaren village in Trenggalek Regency, to mosques and the organizers of one of the activities of the Idul Qurban, namely the slaughter of sacrificial animals. The purpose of using this besek is to replace the plastic packaging that has been used to wrap the meat of sacrificial animals. By replacing plastic bags with plastic bags, the production of plastic bags on the Idul Qurban will also decrease. BUMDes Banyu Lumut is a business unit that used to take up business activities as a savings and loan cooperative. However, the BUMDes Banyu Lumut experienced a long-term debt default phase. Therefore, it is very difficult to provide health or stimulus to BUMDes Banyu Lumut. The proposing team has formulated two main problems, namely a) the unprofessional management of the BUMDes Banyu Lumut which causes management to fail, and b) the Besek Untuk Kurban program which still does not have marketing instruments. As a solution, the proposing team brought up the making of a video profile of Besek Untuk Kurban activities as a means of digital promotion and new knowledge for village youth and BUMDes Banyu Lumut administrators in Tegaren Village. This PIKAT community service activity is carried out using two methods, namely 1) asset-based community development (ABCD) as a method of social approach to the community and 2) production of profile videos with a soft skill approach. Meanwhile, the mandatory outputs include modules, printed and electronic media articles, publications on YouTube, speakers at scientific meetings, the application of science and technology, intellectual property rights and the MBKM program with a minimum conversion of 2 credits for students. The provisional result is that the Bekurban program has managed to collect donations of more than 10 million rupiah this year to provide incentives to besek craftsmen in Tegaren. The team's plan after this is to make a sustainability plan for the Bekurban program through social media.